Expertise in Head and Neck Cutaneous Reconstructive Surgery. Issue 6 (June 2019) - Deng, Min; Higgins, H. William; Lesiak, Kendra; Decker, Ashley B.; Regula, Christie G.; Stevenson, Mary L.; Raphael, Brian; Depry, Jennifer; Scott, Jeffrey F.; Bangash, Haider; Ochoa, Shari A.; Ibrahimi, Omar A.; et al.
Abstract : BACKGROUND: The management of skin cancers has evolved with the development of Mohs micrographic surgery and a greater emphasis on surgical training within dermatology. It is unclear whether these changes have translated into innovations and contributions to the reconstructive literature. OBJECTIVE: To assess contributions from each medical specialty to the cutaneous head and neck oncologic reconstructive literature. METHODS: The authors conducted a systematic review of the head and neck reconstructive literature from 2000 through 2015 based on a priori search terms relating to suture technique, linear closure, advancement, rotation, transposition and interpolation flaps, and identified the specialty of the senior authors. RESULTS: The authors identified 74, 871 articles, of which 1, 319 were relevant. Under suture technique articles, the senior authors were primarily dermatologists (58.2%) and plastic surgeons (20.3%). Under linear closure, the authors were dermatologists (48.1%), plastic surgeons (22.2%), and otolaryngologists (20.4%). Under advancement and rotation flaps, the senior authors were plastic surgeons (40.5%, 38.9%), dermatologists (38.1%, 34.2%), and otolaryngologists (14.4%, 21.6%). Under transposition and interpolation flaps, the senior authors were plastic surgeons (47.3%, 39.4%), dermatologists (32.3%, 27.0%), and otolaryngologists (15.3%, 23.4%). CONCLUSION: The primary specialties contributing to the cutaneous head and neck reconstructive literature are plastic surgery, dermatology, and otolaryngology.